Pragmatic Aspects of Definition in Technical Terms Dictionary - Fitri Amilia; Kisyani Laksono; Budinuryanta Yohanes (Budapest International Research and Critics University, 2018)
The Dictionary of Technical Terms has not shown any significant development on its existence. This dictionary has never been revised since its first publication in 1985 by the National Institute of Language. The dictionary which was presented in KBBI Daring has not also shown any significant changes. The means of defining terms are found to be similar to those of the common dictionary. It is evidenced that there has been no formula yet to define in the dictionary of technical term. This study aims to describe the pragmatic aspects of definition which is the distinctive feature in defining lemma in the dictionary of technical term. Nine different technical term dictionaries published in 1985 by Pusat Pembinaan dan Pengembangan Bahasa were taken as the sources of data to find out about definian and definiandum. Data were gathered through documenting and synthesizing the pragmatic aspects of definian. Pragmasematic approach is the basis of the pragmatic aspects found in the dictionary of technical term. The data were then analyzed using content analysis of similarities and distributions of the definian. The results showed that the pragmatic aspects can be seen from the citation of pragmatic features related to the user’s need while the use of semantic aspects still do exist. The blend of these two is called as pragmasemantic. The findings of this pragmasemantic are indicated by the existence of context setting features, participants, ends, norms, genre, and evidence contexts. This type of pragmasemantic conception consists of a single definian. The findings of this conception is expected to help developing the dictionary of technical terms into learners’ dictionary in which it emphasizes the contextual features of a lemma to assist the learners in grasping the lemma more precisely.